Effects of altitude on thyroid disorders according to Chinese three-rung, ladder-like topography: national cross-sectional study - Boshen Gong; Youmin Wang; Jin-an Zhang; Qiao Zhang; Jiajun Zhao; Jiashu Li; Xichang Wang; Yutong Han; Ziwei Yu; Chenyu Zhang; Bingcong Peng; Yumin Xing; et al. (BMC Public Health, 2024)
Abstract Background Chinese topography appears a three-rung ladder-like distribution of decreasing elevation from northwest to southeast, which is divided by two sloping edges. Previous studies have reported that prevalence of thyroid diseases differed by altitude, and geographical factors were associated with thyroid disorders. To explore the association between three-rung ladder-like regions and thyroid disorders according to unique Chinese topographic features, we conducted an epidemiological cross-sectional study from 2015–2017 that covered all 31 mainland Chinese provinces. Methods A total of 78,470 participants aged ≥ 18 years from a nationally representative cross-sectional study were included. Serum thyroid peroxidase antibody, thyroglobulin antibody, and thyroid-stimulating hormone levels; urine iodine concentration; and thyroid volume were measured. The three-rung ladder-like distribution of decreasing elevation from northwest to southeast in China was categorized into three topographic groups according to elevation: first ladder, > 3000 m above sea level; second ladder, descending from 3000—500 m; and third ladder, descending from 500 m to sea level. The third ladder was further divided into groups A (500–100 m) and B (< 100 m). Associations between geographic factors and thyroid disorders were assessed using linear and binary logistic regression analyses. Results Participants in the first ladder group were associated with lower thyroid peroxidase (β = -4.69; P = 0.00), thyroglobulin antibody levels (β = -11.08; P = 0.01), and the largest thyroid volume (β = 1.74; P = 0.00), compared with the other groups. The second ladder group was associated with autoimmune thyroiditis (odds ratio = 1.30, 95% confidence interval [1.18–1.43]) and subclinical hypothyroidism (odds ratio = 0.61, 95%confidence interval [0.57–0.66]) (P < 0.05) compared with the first ladder group. Group A (third ladder) (500–100 m) was associated with thyroid nodules and subclinical hypothyroidism (P < 0.05). Furthermore, group B (< 100 m) was positively associated with autoimmune thyroiditis, thyroid peroxidase and thyroglobulin antibody positivity, and negatively associated with overt hypothyroidism, subclinical hypothyroidism, and goiter compared with the first ladder group(P < 0.05). Conclusion We are the first to investigate the association between different ladder regions and thyroid disorders according to unique Chinese topographic features. The prevalence of thyroid disorders varied among the three-rung ladder-like topography groups in China, with the exception of overt hyperthyroidism.